AKIBAT HUKUM TERHADAP PELAKU USAHA YANG MELAKUKAN PELANGGARAN HAK ATAS MEREK - Biela, Desy Salsa; Rosando, Abraham Ferry (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Brand is an important thing that is owned by business actors and is often said to be an asset of a business. For this reason, one of the intellectual property rights that the state is required to protect is the mark. Law No. 8 of 1999 Concerning Consumer Protection and Law No. 20 of 2016 Concerning Marks and Geographical Indications control brand rules in Indonesia. However, even though it has been protected, various trademark protections still occur and are mostly carried out by business actors. This study aims to investigate the legal consequences and accountability of business actors who abuse trademark rights. This study uses normative research methods and qualitative research approaches. The study's findings demonstrate that business actors who violate trademark rights may face civil or criminal liability from the original brand owner. The responsibility of business actors who violate trademark rights is regulated in the Trademark Law where the perpetrators can be subject to prison sanctions or witness compensation